A comprehensive method to increase yield and narrow the yield gap of winter wheat for sustainable intensification. (27th January 2022) - Liu, Yuli; Zhang, He; Li, Guicai; Sun, Xiaofang; Wang, Meng
Abstract: BACKGROUND: The agricultural production system is facing increasing demand pressure and environmental pressure. Green and efficient production methods are urgently needed in order to further enhance the yield of winter wheat and reduce the negative impact on the environment. Here, we analyzed the potential yield and yield gap of winter wheat in Shandong Province of China from 1981 to 2009. Meanwhile, we specified the effects of sowing time, irrigation and fertilization scheme, and variety characteristics on winter wheat. RESULTS: In the past 29 years, the yield gap in most areas of Shandong has become smaller, because the actual yield has increased and the potential yield has changed little under the background of climate change. In addition, it is found that delaying sowing date is beneficial to increase yield by helping winter wheat avoid adverse climate conditions. Also, an irrigation amount of 240 mm and nitrogen application amount of 180–210 kg ha −1 are best to maintain high yield, high resource utilization rate and low environmental pollution in this area. These suggested levels are lower than those currently used by many local farmers. Wheat varieties with longer grain‐filling period and photoperiod response, higher grain‐filling rate and grain weight were more adaptable to climate change. CONCLUSION: Improving agronomic management measures can significantly increase the yield of winter wheat and narrow the yield gap. This study can provide valuable information for improving the production potential of winter wheat, and for reducing the damage of agricultural activities to the environment. © 2022 Society of Chemical Industry.